Unique Features of the Human Brainstem and Cerebellum - Baizer, Joan S. (Frontiers in Human Neuroscience, 2014)
The cerebral cortex is greatly expanded in the human brain. There is a parallel expansion of the cerebellum, which is interconnected with the cerebral cortex. We have asked if there are accompanying changes in the organization of the precerebellar brainstem structures. We have examined the cytoarchitectonic and neurochemical organization of the human medulla and pons. We studied human cases from the Witelson Normal Brain Collection, analyzing Nissl sections and sections processed for immunohistochemistry for multiple markers including the calcium-binding proteins calbindin, calretinin and parvalbumin, nonphosphorylated neurofilament protein, and the synthetic enzyme for nitric oxide, nitric oxide synthase. We have also compared the neurochemical organization of the human brainstem to that of several other species including the chimpanzee, macaque and squirrel monkey, cat, and rodent, again using Nissl staining and immunohistochemistry. We found that there are major differences in the human brainstem, ranging from relatively subtle differences in the neurochemical organization of structures found in each of the species studied to the emergence of altogether new structures in the human brainstem. Two aspects of human cortical organization, individual differences and left-right asymmetry, are also seen in the brainstem (principal nucleus of the inferior olive) and the cerebellum (the dentate nucleus). We suggest that uniquely human motor and cognitive abilities derive from changes at all levels of the central nervous system, including the cerebellum and brainstem, and not just the cerebral cortex.